Philosophical Analysis of Positivism Article 6 (1) ICCPR in The Construction of Armed Criminal Group Human Rights - Fernando Holqi, Fikri Gali; Thoriqul Widianto, Irfany (Program Studi Magister Kenotariatan Fak. Hukum Univ. Andalas, 2024)
This study aims to identify philosophically and juridically related to the Deconstruction of Article 6 (1) ICCPR in the construction of KKB Human Rights and Deconstruction of Human Rights as positive law on the principles of Positivism Philosophy. This research uses normative (doctrinal) methods with a statutory approach (statute approach), and conceptual approach by implementing primary legal principles covering regional to international law and consisting of theories of positivism philosophical traditions, legal dogma, and other relevant literature. The results of this study show that the government should be able to provide firm action against Criminal Acts of Terrorism, especially KKB in Indonesia because there is the highest principle, namely Salus Populi Suprema Lex Esto, and the conception of human rights as positive law that is irrelevant to the founding father of legal positivism, namely the Philosophy of Positivism.